2018
DOI: 10.1002/humu.23602
|View full text |Cite|
|
Sign up to set email alerts
|

Motor protein binding and mitochondrial transport are altered by pathogenic TUBB4A variants

Abstract: Mutations in TUBB4A have been identified to cause a wide phenotypic spectrum of diseases ranging from hereditary generalized dystonia with whispering dysphonia (DYT-TUBB4A) and hereditary spastic paraplegia (HSP) to leukodystrophy hypomyelination with atrophy of the basal ganglia and cerebellum (H-ABC). TUBB4A encodes the brain-specific β-tubulin isotype, β-tubulin 4A. To elucidate the pathogenic mechanisms conferred by TUBB4A mutations leading to the different phenotypes, we functionally characterized three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Sanger sequencing showed that our patient carries a mutation in TUBB4A (D249N) which was previously identified in other patients (Curiel et al, 2017; Vulinovic et al, 2018) (Figure 1a, left square). We also found a GTT to GTC change in the nucleotide sequence, with no effects on the amino acid (Val) in position 258 (Figure 1a, right square).…”
Section: Resultssupporting
confidence: 76%
“…Sanger sequencing showed that our patient carries a mutation in TUBB4A (D249N) which was previously identified in other patients (Curiel et al, 2017; Vulinovic et al, 2018) (Figure 1a, left square). We also found a GTT to GTC change in the nucleotide sequence, with no effects on the amino acid (Val) in position 258 (Figure 1a, right square).…”
Section: Resultssupporting
confidence: 76%
“…Here, we observed no differences in overexpressed TUBB4A levels between WT and either p.R2G or p.R2W mutations, suggesting that the impaired autoregulation of TUBB4A mRNA does not play a major role in our cell model. This is consistent with the results of previous publications addressing mRNA and protein stability of TUBB4A ( 19 , 20 ). Notably, compared to other tubulin isoforms, TUBB4A does not appear to be susceptible to pharmacologically induced tubulin mRNA autoregulation ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…Plasmids (pER4) expressing GFP-tagged TUBB4A variants and EB3-GFP were previously described ( 20 ). For our recent study, we have modified the plasmids to either tag TUBB4A variants C-terminally with GFP or coexpress with EB3-GFP.…”
Section: Methodsmentioning
confidence: 99%
“…Other minor β-tubulin isotypes (βII-tubulin and βIVα-tubulin) have also been associated with regulating mitochondrial localization specifically in cardiomyocytes [ 66 , 67 , 68 , 69 ], although the mechanisms by which they operate remain unknown. With increasing recognition for the combinatorial manner in which β-tubulin isotypes collectively regulate microtubule functions and microtubule-dependent processes in cells [ 18 , 21 , 70 ], it is likely that the tubulin code regulating mitochondrial dynamics is a complex spatiotemporal network that depends on the local β-tubulin composition.…”
Section: Discussionmentioning
confidence: 99%